Prospective comparison of three risk scoring systems in non‐variceal and variceal upper gastrointestinal bleeding. Issue 4 (April 2016) - Thanapirom, Kessarin; Ridtitid, Wiriyaporn; Rerknimitr, Rungsun; Thungsuk, Rattikorn; Noophun, Phadet; Wongjitrat, Chatchawan; Luangjaru, Somchai; Vedkijkul, Padet; Lertkupinit, Comson; Poonsab, Swangphong; Ratanachu‐ek, Thawee; Hansomburana, Piyathida; et al.
Abstract: Background and Aim: Data regarding the efficacy of the Glasgow Blatchford score (GBS), full Rockall score (FRS) and pre‐endoscopic Rockall scores (PRS) in comparing non‐variceal and variceal upper gastrointestinal bleeding (UGIB) are limited. Our aim was to determine the performance of these three risk scores in predicting the need for treatment, mortality, and re‐bleeding among patients with non‐variceal and variceal UGIB. Methods: During January, 2010 and September, 2011, patients with UGIB from 11 hospitals were prospectively enrolled. The GBS, FRS, and PRS were calculated. Discriminative ability for each score was assessed using the receiver operated characteristics curve (ROC) analysis. Results: A total of 981 patients presented with acute UGIB, 225 patients (22.9%) had variceal UGIB. The areas under the ROC (AUC) of the GBS, FRS, and PRS for predicting the need for treatment were 0.77, 0.69, and 0.61 in non‐variceal versus 0.66, 0.66, and 0.59 in variceal UGIB. The AUC for predicting mortality and re‐bleeding during admission were 0.66, 0.80, and 0.76 in non‐variceal versus 0.63, 0.57, and 0.63 in variceal UGIB. AUC score was not statistically significant for predicting need for therapy and clinical outcome in variceal UGIB. The GBS ≤ 2 and FRS ≤ 1 identified low‐risk non‐variceal UGIB patients for death and re‐bleeding during hospitalization. Conclusion: In contrast to non‐variceal UGIB, the GBS, FRS, and PRS were not precise scores for assessing the need for therapy, mortality, and re‐bleeding during admission in variceal UGIB.